2020
DOI: 10.1159/000507293
|View full text |Cite
|
Sign up to set email alerts
|

Oral S-1 with 24-h Infusion of Irinotecan plus Bevacizumab versus FOLFIRI plus Bevacizumab as First-Line Chemotherapy for Metastatic Colorectal Cancer: An Open-Label Randomized Phase II Trial

Abstract: Background: FOLFIRI plus bevacizumab have been widely used as first-line treatment for metastatic colorectal cancer (mCRC). Pharmacokinetics and pharmacodynamics suggested a low dose of irinotecan given as a long-term infusion is expected to enhance antitumor activity. We conducted a randomized phase II study to compare oral S-1 with a 24-h infusion of irinotecan plus bevacizumab versus FOLFIRI plus bevacizumab. Methods: The subjects comprised 120 chemotherapy-naïve patients with mCRC. The study group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…As the most potent proangiogenic factor known, vigorous expression of VEGF is observed in tumor patients [ 20 , 21 ]. In the current study, the VEGF levels were reduced in both groups after treatment, with significantly lower levels in the study group than in the control group ( P < 0.05), which was similar to the findings of Sadahiro et al [ 22 ], suggesting that bevacizumab and gemcitabine combined with cisplatin for esophageal cancer could reduce VEGF levels and promote apoptosis of cancer cells. Cyfra21-1 is a marker of epithelial cell carcinogenesis that exists in the plasma as an oligomer, which is proteolytically cleaved and enters the circulation upon cell carcinogenesis [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…As the most potent proangiogenic factor known, vigorous expression of VEGF is observed in tumor patients [ 20 , 21 ]. In the current study, the VEGF levels were reduced in both groups after treatment, with significantly lower levels in the study group than in the control group ( P < 0.05), which was similar to the findings of Sadahiro et al [ 22 ], suggesting that bevacizumab and gemcitabine combined with cisplatin for esophageal cancer could reduce VEGF levels and promote apoptosis of cancer cells. Cyfra21-1 is a marker of epithelial cell carcinogenesis that exists in the plasma as an oligomer, which is proteolytically cleaved and enters the circulation upon cell carcinogenesis [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…An overview of studies and median PFS data are presented in Appendix A5. Except for the study by Kim et al [19], which reported a median time to progression of 7.4 months for the control arm versus 6.1 months for the S-1-based arm, the other three studies reported a comparable time to progression with differences ranging from 0.2 to 0.7 months [21,22,24]. All four studies reported no statistically significant difference in PFS between 5-FU/ capecitabine-based versus S-1-based therapy (P > 0.05).…”
Section: Progression-free Survivalmentioning
confidence: 96%
“…For the primary outcome, five studies were rated as low risk of bias [10,16,19,20,26], whereas five other studies were rated as some concerns for risk of bias because of concerns arising from the randomisation process [22,24], missing outcome data [21], measurement of the outcome [25,27] and/or selection of the reported results [21,22] (Appendix A3). Visual inspection of the funnel plots indicated no apparent asymmetry, and therefore, we assume a low risk of publication bias (Appendix A4).…”
Section: Literature Search and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations